Hidrólise enzimática na fabricação de melado de cana-de-açúcar - Emídio, João Expedito (2016)
The objective of this study was to evaluate the production of sugar cane syrups using enzymes of Saccharomyces cerevisiae from bakery yeast. The effect of theconcentration of yeast, reaction time and temperature for the hydrolysis of crystal sugar solution (VHP) in the physico-chemical properties and sucrose inversion rate were evaluated. Subsequently, the selected parameters were applied in order to hydrolyze sugarcane juice from three different seasons of the year. Finally, the optimized parameters were used to produce the syrups and their physico-chemical and sensory properties were compared to the syrup produced without sucrose hydrolysis. Physico-chemical analyzes showed percentage of total soluble solids (TSS), varying between 74.60 and 76.37%, reducing sugars (RS) between 12.00 and 27.54%, total reducing sugars (TRS) from 67.92 to 70.34%, pH between 4.95 and 4.97, sucrose inversion rate between 14.40 to 39.35%, water activity of 0.75 to 0.78 and instrumental color (L*, a*, b* parameters) from 21.50 to 24.61, 1.04 to 2.45, and 1.12 to 4.53, respectively. The attributes obtained from descriptive quantitative analysis (QDA) were color, brightness, sugarcane syrup and yeast aroma, sweet and acid taste, viscosity. The untreated syrup was the least preferred. Results indicate a viable and low cost solution for syrup production with a reducing sugar content of about 30%, ensuring a better stability in relation to sucrose crystallization, which is frequently associated as a negative aspect of product quality.